Memoria del Derecho y disciplinas jurídicas. Estudios - Álvarez Alonso, Clara (Historia del Derecho, 2022)
This work collects the presentations made at the III International Seminar Memory of Law and Legal Disciplines (XIX-XX centuries) held on May 25 and 26, 2022 at the Santa María de la Rábida Campus of the International University of Andalusia, in Palos de la Frontera, Huelva. The following pages discuss the lives of legal scholars as well as the emergence of legal disciplines and legal education in Spain in the period spanning from the Moyano Law of Public Instruction (1857) to the University Reform Law (1983).